How similar is similar enough? A sufficient similarity case study with Ginkgo biloba extract. (August 2018) - Catlin, Natasha R.; Collins, Bradley J.; Auerbach, Scott S.; Ferguson, Stephen S.; Harnly, James M.; Gennings, Chris; Waidyanatha, Suramya; Rice, Glenn E.; Smith-Roe, Stephanie L.; Witt, Kristine L.; Rider, Cynthia V.
Abstract: Botanical dietary supplements are complex mixtures that can be highly variable in composition and quality, making safety evaluation difficult. A key challenge is determining how diverse products in the marketplace relate to chemically and toxicologically characterized reference samples (i.e., how similar must a product be in order to be well-represented by the tested reference sample?). Ginkgo biloba extract (GBE) was used as a case study to develop and evaluate approaches for determining sufficient similarity. Multiple GBE extracts were evaluated for chemical and biological-response similarity. Chemical similarity was assessed using untargeted and targeted chemistry approaches. Biological similarity was evaluated using in vitro liver models and short-term rodent studies. Statistical and data visualization methods were then used to make decisions about the similarity of products to the reference sample. A majority of the 26 GBE samples tested (62%) were consistently determined to be sufficiently similar to the reference sample, while 27% were different from the reference GBE, and 12% were either similar or different depending on the method used. This case study demonstrated that approaches to evaluate sufficient similarity allow for critical evaluation of complex mixtures so that safety data from the tested reference can be applied to untested materials. Graphical abstract: Highlights: Botanical dietary supplements with similar labels can vary widely in content. Approaches to determine sufficient similarity of complex mixtures are presented. Chemical and biological activity data are integrated for similarity evaluation. Ginkgo biloba extract is used as a case study to illustrate methods. While a majority of Ginkgo samples were similar, some were notably different.